Bi nonstoichiometry and composition engineering in (1 − x)Bi1+yFeO3+3y/2 − xBaTiO3 ceramics. Issue 93 (21st September 2016) - Zheng, Ting; Ding, Yi; Wu, Jiagang
Abstract : Rhombohedral–pseudocubic (R–C) phase boundary was formed in the ceramics through the addition of BaTiO3 . Enhanced piezoelectricity and ferroelectricity can be achieved in a wide composition range due to the formation of R–C phase boundary. Abstract : Bi is easily evaporated during the preparation of BiFeO3, and moreover its phase structure and electrical properties can also be modified by doping BaTiO3 . In this work, the effects of Bi nonstoichiometry as well as BaTiO3 on the phase purity, microstructure, and electrical properties of (1 − x )Bi1+ y FeO3+3 y /2 − x BaTiO3 (0.25 ≤ x ≤ 0.35 and −0.1 ≤ y ≤ 0.25) ceramics were studied. A rhombohedral–pseudocubic (R–C) phase boundary was formed in the ceramics with a wide composition range of x = 0.30 and −0.05 ≤ y ≤ 0.15, leading to an enhanced piezoelectricity ( d 33 ∼ 180 pC/N). In addition, one can find that dense microstructure as well as the improvement of Curie temperature ( T C ∼ 506 °C) and thermal stability of piezoelectricity ( T a = 400 °C) can be achieved in the ceramics with excess Bi ( x = 0.30, y = 0.05) with respect to the ones with Bi deficiency. We expect that the investigation on Bi nonstoichiometry and the addition of BaTiO3 will point out an effective method to fabricate high-performance BFO-based ceramics.